Examining the Ethics of Government-Organized Nongovernmental Organizations (GONGOs). (12th September 2017) - Kleinschmit, Stephen W.; Edwards, Vickie
Abstract : This article explores the ethics of an increasingly pervasive form of third-sector organization, the government-organized nongovernmental organization. GONGOs are an important means of projecting state power in a broad spectrum of foreign policy and national security contexts, from boardrooms to battlefields. As these organizations become increasingly professionalized, a need emerges for defining the bounds of their ethical conduct. Because the nature of their authority evolves in an age of public value governance, their institutional ethos also requires evaluation. This article examines existing principles of government, nonprofit, military, and private military contractor ethics to assist in defining the bounds of GONGO ethics. It uses international law to provide guidance on ethical standards for organizations supporting noncombat national security and foreign policy missions, provides prescriptive guidance for their operation, and contemplates questions for future research.